Reological and thermodynamical properties of mixtures containing [BMIM][Cl] and glycerol. - Espinoza Velasquez, Luis Alonso (2018)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Química, Programa de Pós-Graduação em Tecnologias Química e Biológica, 2018.